PEWARNAAN SERAT DAUN DOYO MENGGUNAKAN PEWARNA ALAMI DARI EKSTRAK DAUN KETAPANG - Nursilawati, Nursilawati; Awaliyah, Nabilah Nailah; Pakaenoni, Frederich; Larasati, Herlin Alfiana; Hartandi, Dimas; Rahmadani, Agung; Wirhanuddin, Wirhanuddin; Sukemi, Sukemi (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Ulap Doyo is a traditional woven fabric of the Dayak Benuaq tribe in East Kalimantan. Ulap Doyo is made from doyo (Curculigo latifolia) leaf fibers with the base color of whitish cream. Natural dye is used to create patterns. Ketapang (Terminalia catappa L.) leaves contain tannins that can be used as natural dyes. This study aimed to determine the color change of doyo leaf fibers dyed using aqueous ketapang leaf extract. The natural dye was extracted by decoction technique with distilled water as solvent. Tannin content was analyzed using phytochemical tests and permanganometric titration. The dyeing process used the dye bath technique at 92°C of dyeing temperature, 1:100 (w/v) of MLR, and 135 minutes of dyeing time. Before dyeing process, the extract and fibers were treated using 5 mL of 1 M acetic acid (AA) and 5 mL of 1 M ammonia (Am). The color change of the dyed fibers: untreated fiber - untreated extract (UF-UE), treated fiber - untreated extract (TFAA-UE, TFAm-UE), untreated fiber - treated extract (UF-TEAA, UF-TEAm), and treated fiber - treated extract (TFAA-TEAA, TFAm-TEAm) were measured using ImageJ application and shown in term of ∆I. This research results shows that the extract was dark brown solution with 0,280 ± 0,001 % (w/w) of tannin content. The color shade of the dyed doyo leaf fibers is pale brown to brown. The treatment of the extract using acetic acid (UF-TEAA) produce the highest colour shade and ∆I value. This study shows that the ketapang leaf extract can be used as dye for ulap doyo. Keywords : ulap doyo, Curculigo latifolia, Terminalia catappa L., dyeing bath technique